'A nice idea but....': Implementing a reflective supervision model in the National Probation Service in England and Wales. Issue 5 (3rd September 2022) - Ainslie, Sam; Fowler, Andrew; Phillips, Jake; Westaby, Chalen
ABSTRACT: Despite significant research and literature relating to the role of critically reflective practice and staff supervision in 'helping professions', there has been less attention given to probation practice. This article addresses this gap by presenting the findings from a study that explores the implementation of a reflective model of staff supervision in the National Probation Service. Utilising a mixed-methods research design including a survey and semi-structured interviews with managers and front-line practitioners, the study sheds light on probation staff's experience of reflective supervision and manager perspectives of implementing the model. Overall, we find that probation staff are supportive of the ethos and underpinning principles of the reflective supervision model. However, our participants raised important barriers to implementation, most notably a lack of time and perceived tension between the managerial and developmental aspects of the supervisor role. We conclude by arguing that the Probation Service needs to address these barriers to enable reflective supervision to realise its potential to protect practitioner emotional well-being, support-positive outcomes for individuals subject to probation intervention and develop practitioner professionalism, empowerment, and autonomy.